1995
DOI: 10.1007/bf03349709
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sodium valproate on luteinizing hormone secretion in women with polycystic ovary disease

Abstract: The aim of this study was to examine whether modulation of the GABA-ergic system (with sodium valproate) affects gonadotropin secretory frequency and amplitude in women with polycystic ovarian syndrome (PCOS). Six women aged 25 +/- 2 years with diagnosed PCOS and six healthy women aged 26 +/- 2 years at day 7-11 of menstrual cycle were included in the study. Sodium valproate 1200 mg p.o./day (600 mg t.i.d.) was administered for five days in both groups. Efficacy of treatment was assessed in women with PCOS by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…This low level of research activity has been due partly to blood samples, and partly to the lack of a broad group of safe, specific drugs allowing external control of this interaction. We have reported previously that VPA-induced alteration of the GABAergic system has no significant effect on pulsatile LH secretion by normal women during the late follicular phase (22) and mid-late luteal phase (23) (and therefore no effect on mean serum LH concentrations during these periods), a finding in keeping with the results of other researchers (41)(42)(43). The results on ovariectomized women now reported appear to confirm that, in this respect as in others, the neurotransmitter-mediated mechanisms controlling the hypothalamo-pituitary axis in humans differ from those operating in rats.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This low level of research activity has been due partly to blood samples, and partly to the lack of a broad group of safe, specific drugs allowing external control of this interaction. We have reported previously that VPA-induced alteration of the GABAergic system has no significant effect on pulsatile LH secretion by normal women during the late follicular phase (22) and mid-late luteal phase (23) (and therefore no effect on mean serum LH concentrations during these periods), a finding in keeping with the results of other researchers (41)(42)(43). The results on ovariectomized women now reported appear to confirm that, in this respect as in others, the neurotransmitter-mediated mechanisms controlling the hypothalamo-pituitary axis in humans differ from those operating in rats.…”
Section: Discussionsupporting
confidence: 89%
“…In particular, hardly any work has been done on the possible relationship ofthe GABAergic system to the pulsatility of LH secretion (22,23,42). This low level of research activity has been due partly to blood samples, and partly to the lack of a broad group of safe, specific drugs allowing external control of this interaction.…”
Section: Discussionmentioning
confidence: 97%
“…Early studies in normal (short-term VPA use) and epileptic (long-term VPA use) populations did not indicate an effect of VPA on prolactin [150,[167][168][169]. In 1988, Bilo et al found increased concentrations of prolactin in a female epileptic population but could not definitively relate it to AED use, or VPA use in particular [139].…”
Section: Prolactinmentioning
confidence: 92%
“…Popovic et al studied endocrine status in a healthy population administered VPA over the course of two or five days and did not find any changes in FSH or LH secretion [150]. In a follow-up study, however, the authors found that postmenopausal women not on hormone replacement therapy and healthy reproductive-aged women in their mid-luteal phase both exhibited LH suppression in acute response to VPA administration, whereas postmenopausal women receiving hormone replacement therapy showed no acute change in LH or FSH.…”
Section: Gonadotropinsmentioning
confidence: 96%
See 1 more Smart Citation